Metabolites of traditional Chinese medicine targeting PI3K/AKT signaling pathway for hypoglycemic effect in type 2 diabetes - Feng, Yuhan; Ren, Yan; Zhang, Xia; Yang, Songqin; Jiao, Qian; Li, Qiuhong; Jiang, Wenwen (Frontiers in Pharmacology, 2024)
Type 2 diabetes mellitus is a chronic metabolic disease characterized by insulin resistance, with high morbidity and mortality worldwide. Due to the tightly intertwined connection between the insulin resistance pathway and the PI3K/AKT signaling pathway, regulating the PI3K/AKT pathway and its associated targets is essential for hypoglycemia and the prevention of type 2 diabetes mellitus. In recent years, metabolites isolated from traditional Chinese medicine has received more attention and acceptance for its superior bioactivity, high safety, and fewer side effects. Meanwhile, numerous in vivo and in vitro studies have revealed that the metabolites present in traditional Chinese medicine possess better bioactivities in regulating the balance of glucose metabolism, ameliorating insulin resistance, and preventing type 2 diabetes mellitus via the PI3K/AKT signaling pathway. In this article, we reviewed the literature related to the metabolites of traditional Chinese medicine improving IR and possessing therapeutic potential for type 2 diabetes mellitus by targeting the PI3K/AKT signaling pathway, focusing on the hypoglycemic mechanism of the metabolites of traditional Chinese medicine in type 2 diabetes mellitus and elaborating on the significant role of the PI3K/AKT signaling pathway in type 2 diabetes mellitus. In order to provide reference for clinical prevention and treatment of type 2 diabetes mellitus.